Improved photovoltaic and grain boundary characteristics of single elementary target-sputtered Cu2ZnSnSe4 thin films by post sulfurization/selenization process. (22nd May 2015) - Jo, Yeon Hwa; Jang, Jin Woo; Mohanty, Bhaskar Chandra; Kang, Han Byul; Cho, Yong Soo
Abstract: A potential way to improve the quality of Cu2 ZnSnSe4 absorber thin film by a one step process of sputtering using a single elementary target is proposed for thin film solar cells. As critical parameters, different S/Se ratios and grain boundary characteristics are achieved by adjusting sequential sulfurization and selenization post-treatment. The simple sulfurization of as-deposited film at 530 °C in H2 S is not effective in raising the performance but the additional Se annealing at a shorter duration of 5 min improves conversion efficiency from 0.12 to 3.21% with a drastic increase of the open circuit voltage. Positively-charged grain boundaries with narrow potential peaks seem to play a critical role for effective exciton separation and higher efficiency. The improvement is also understood as related to well-defined microstructures and the variable optical band gap.